2019
DOI: 10.1080/21691401.2019.1594852
|View full text |Cite
|
Sign up to set email alerts
|

BMP-2-releasing gelatin microspheres/PLGA scaffolds for bone repairment of X-ray-radiated rabbit radius defects

Abstract: View related articles View Crossmark data Citing articles: 4 View citing articles BMP-2-releasing gelatin microspheres/PLGA scaffolds for bone repairment of X-ray-radiated rabbit radius defects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Furthermore, locally high doses of rhBMP-2 can cause significant adverse reactions [57,58]. Gelatin microspheres have been demonstrated to be an ideal sustainedrelease carrier for rhBMP-2 in previous studies [38,59]. In addition, the low immunogenicity, good biocompatibility, and biodegradability of gelatin have been demonstrated [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, locally high doses of rhBMP-2 can cause significant adverse reactions [57,58]. Gelatin microspheres have been demonstrated to be an ideal sustainedrelease carrier for rhBMP-2 in previous studies [38,59]. In addition, the low immunogenicity, good biocompatibility, and biodegradability of gelatin have been demonstrated [60].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an appropriate carrier for rhBMP-2 is needed to achieve stable and sustained release. Xia et al [38] used gelatin microspheres to encapsulate BMP-2 on a poly(lactic-co-glycolic acid) scaffold and achieved sustained release. In addition, the coating also enhanced the proliferation and osteogenesis of rabbit bone mesenchymal stem cells (BMSCs) in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…They found that BMP-2 scaffolds increased osteogenesis and proliferation of BMSCs in vitro. In vivo, BMP-2 scaffolds showed significantly higher osteogenic potential and sustained release of the GF [ 58 ]. Another GF commonly used in tissue engineering is VEGF.…”
Section: Desired Characteristics Of 3d Scaffoldsmentioning
confidence: 99%
“…Recently, growth factors have been carried in GMs to be delivered. Compared with other forms of carriers, the advantages of microspheres are that they can extend the h55alf-life of growth factors that they carry [34], and consequently improve the therapeutic effect in vivo [22,35]. GMs loading PRP has been applied for tissue regeneration, such as treatment in the osteoarthritis in rabbit [36], treatment for the degenerated intervertebral disc (IVD) model in rabbit [37,38], bone regeneration in rabbit [39,40], and treatment of ischaemic disorders in mouse [41].…”
Section: Ivyspringmentioning
confidence: 99%